Variables influencing students' learning motivation: critical literature review - Ishida, Ayame; Sekiyama, Takashi (Frontiers in Education, 2024)
This study presents a critical literature review exploring the variables influencing student learning motivation between 2017 and 2023. The study analyzes 84 empirical studies to identify trends and patterns across diverse demographics, including varied age groups and cultural backgrounds, focusing on contrasting Eastern and Western educational contexts. This study aims to fill the existing gap by examining a wider range of populations in recent years to assess the relationship between learning motivation and the factors that influence it. Six pivotal factors influencing learning motivation were identified: psychological values, cognitive factors, social and environmental influences, demographic factors, academic background and study habits, and interventions and programs, each contributing uniquely to the understanding of student motivation. Moreover, the findings underscore the predominance of psychological values in Eastern countries, whereas the Western literature focuses on social and environmental influences. This review acknowledges the nuanced relationship between cultural constructs and learning motivation research, emphasizing the need for culturally sensitive educational policies and practices. Additionally, by taking into account the recent advancements in technology and the effects of global events such as the COVID-19 pandemic, this study considers additional motivational factors, presenting a holistic view that could inform future educational interventions and academic policies. For example, the revised categorization in our study emphasizes the complex and interconnected nature of the factors affecting learning motivation, highlighting the interaction among psychological, social, cognitive, and demographic dimensions.